Discourse Analysis on the Cohesive Devices in the Graduate Student Thesis - Halimah, Mujammilatul; Hidayat, Didin Nuruddin; Alek, Alek; Baker, Shirley (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
One of the significant elements of writing skills is cohesion. Cohesion is a concept that refers to the connection and smooth relationship between elements in a text or discourse. In the context of writing, cohesion is the ability to connect ideas, sentences, or paragraphs so that they form a coherent and easy-to-understand whole. Cohesion plays an important role in ensuring that a text has a logical flow and can be understood well by readers. Therefore, the purpose of this study is to investigate cohesive devices found in graduate students' theses. It is the case that the language that is utilized the most frequently in print, electronic, and internet media is English. Writing in English is becoming an increasingly crucial ability, particularly in the academic sphere, as English continues to prevail as the universal language of choice for scientific research and publications. To comprehensively analyze how cohesive devices are utilized in the thesis text, the present study employs a qualitative descriptive method. Coding was used to analyze the data from the theses written by one graduate students. The categories of text and texture, cohesion, grammatical cohesion, and lexical cohesion were considered during the analysis. Based on the findings of this study, grammatical coherence was examined in eight sentences, while lexical cohesion was examined in four sentences.